2019
DOI: 10.1093/beheco/arz139
|View full text |Cite
|
Sign up to set email alerts
|

Natal conditions, lifespan and lifetime reproductive success of European blackbirds

Abstract: Even though much has been published in recent years on the factors affecting the lifespan and lifetime reproductive success of birds, there are still gaps in our knowledge. Here, we present the results of a long-term study of European blackbirds which examined the effect of natal conditions on lifespan and lifetime reproductive success (expressed by the number of fledglings) of 152 nestlings (72 males and 80 females) ringed in the Stefan Żeromski Park in Szczecin (NW Poland). We have complete information regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
4
1
Order By: Relevance
“…The most unexpected result obtained in this study was that precipitation during the first 30 days of life is negatively related to fledgling survival. Food availability is the most important factor impacting fledgling survival 6 , 11 , but because precipitation affects food availability for Blackbirds 21 , 22 , 43 , 44 , this result did not support our hypothesis. Similar results were obtained for northern wheatears ( Oenanthe oenanthe ), where rainfall during parental care reduces not only fledgling survival but also their recruitment probability.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The most unexpected result obtained in this study was that precipitation during the first 30 days of life is negatively related to fledgling survival. Food availability is the most important factor impacting fledgling survival 6 , 11 , but because precipitation affects food availability for Blackbirds 21 , 22 , 43 , 44 , this result did not support our hypothesis. Similar results were obtained for northern wheatears ( Oenanthe oenanthe ), where rainfall during parental care reduces not only fledgling survival but also their recruitment probability.…”
Section: Discussioncontrasting
confidence: 68%
“…The time of hatching strongly impacts the condition and survival of many bird species 40 , including this population of Blackbirds 22 . Offspring that fledge earlier in the season may benefit from milder environmental conditions, more plentiful food, reduced intraspecific competition for resources, as well as lower predation rates and parasitism (see 41 for a review).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found, however, that paternal age was almost non-linearly positively related to filial breeding success, which does not falsify the “good genes” hypothesis. We think that a male’s advanced age could be a signal of his high quality (the most successful males survive better and live longer ( Jankowiak, Zyskowski & Wysocki, 2018 ); in this population, lifespan is generally closely related to higher lifetime reproductive success ( Wysocki et al 2019 ; Zyskowski, 2015 ). The observed slight decline in the breeding success of sons of >6 years old fathers appears to be acting as a trade-off between the costs of senescence and the benefits of “good genes”: after the sixth year of life, the costs of paternal senescence outweigh the benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined possible offspring sex bias in an open-cup nesting passerine—the European Blackbird Turdus merula (henceforth Blackbird). There were several reasons for this: (1) Blackbirds are socially monogamous, dimorphic birds (the only Turdus species with clear differences in plumage colouration), where adult males are bigger than adult females ( Piliczewski, Ł& Wysocki, 2018 ); female mating preference could therefore depend on a male phenotypic trait, or else a single male trait, such as age, could affect male mating opportunities; (2) high-quality males of this species engage in extra-pair copulations ( Wysocki & Halupka, 2004 ); (3) the population studied exhibits many different breeding strategies in order to maximise breeding success ( Wysocki, 2004 ; Wysocki, 2005 ; Wysocki, 2006 ; Wysocki & Walasz, 2004 ; Wysocki & Jankowiak, 2018 ); (4) egg size in this species has been found to be sexually dimorphic—larger eggs contain male embryos ( Martyka et al, 2010 )—and hatching in this species is highly asynchronous ( Magrath, 1989 ), so we can expect a relationship between offspring sex and hatching sequence, and older females should produce smaller eggs because of their poor condition due to senescence; (5) chick productivity in the target urban population is low and lifetime breeding success is subject to considerable variance: during a 21-year study, just 7% of males and 16% of females raised 50% of all fledglings; the less numerous, oldest individuals are the birds with the highest lifetime breeding success ( Wysocki et al, 2019 ; Zyskowski, 2015 ). A few studies have shown that age is a significant factor influencing reproductive life-history traits of blackbirds ( Desrochers, 1992a ; Desrochers, 1992b ; Desrochers & Magrath, 1993 ; Streif & Rasa, 2001 ).…”
Section: Introductionmentioning
confidence: 99%